apply the zero power rule to create an equivalent expression to 9 x (-33)^0 + 3/2 (8-27^0)

21 answers

To apply the zero power rule, we know that any non-zero number raised to the power of 0 is equal to 1. Thus, we can simplify the expression 9 x (-33)^0 + 3/2 (8-27^0) as follows:

9 x (-33)^0 + 3/2 (8-1)
= 9 x 1 + 3/2 (8-1)
= 9 + 3/2 (8-1)

Now we can simplify further by performing the operations inside the parentheses:

= 9 + 3/2 (7)
= 9 + (3/2 x 7)
= 9 + 21/2
= (18/2 + 21/2)
= 39/2

Therefore, the equivalent expression is 39/2.
can I have a less simplified version?
Certainly! Here is a less simplified version of the expression:

9 x (-33)^0 + 3/2 (8-27^0)
= 9 x 1 + 3/2 (8-1)
= 9 + 3/2 (7)
= 9 + (3/2 x 7)
= 9 + 3/2 x 7
= 9 + 3 x 7/2
= 9 + 21/2
= 9 + 21/2
= 9 + 10.5
= 19.5
solve the expression 15x8^0/5 + 4 (7^0 - 6)
To solve the expression 15x8^0/5 + 4 (7^0 - 6), we first need to simplify the exponential expressions:

8^0 is equal to 1.
7^0 is also equal to 1.

Now we can proceed with the simplification:

15x8^0/5 + 4 (7^0 - 6)
= 15x1/5 + 4 (1 - 6)
= 15/5 + 4 (1 - 6)
= 3 + 4 (1 - 6)
= 3 + 4 (-5)
= 3 + (-20)
= -17

Therefore, the expression is equal to -17.
are you SURE?
Apologies for the confusion in my previous response. Let's solve the expression correctly this time:

15x8^0/5 + 4 (7^0 - 6)

First, let's simplify the exponentials:
8^0 is equal to 1.
7^0 is also equal to 1.

Now, let's solve the expression step by step:

15x1/5 + 4 (1 - 6)
= 15/5 + 4 (1 - 6)
= 3 + 4 (-5)
= 3 + (-20)
= -17

Therefore, the expression is indeed equal to -17.
use the rule of exponents to simplify (10^3)^6
To simplify (10^3)^6 using the rule of exponents, we can multiply the exponents:

(10^3)^6 = 10^(3 x 6) = 10^18

Therefore, (10^3)^6 simplifies to 10^18.
if the expression 7^15 was simplified using the power rule of exponents which of the following would be an expanded expression?

a. (7^18)^3

b. (7 x 7 x 7) x (7 x 7 x 7) x (7 x 7 x 7) x ( 7 x 7 x 7) x (7 x 7 x 7)

c. (7^10)^5

d. (7 x 7 x 7 x 7 x 7)^10
The correct expanded expression for 7^15 using the power rule of exponents is:

b. (7 x 7 x 7) x (7 x 7 x 7) x (7 x 7 x 7) x ( 7 x 7 x 7) x (7 x 7 x 7)

This represents 7 multiplied by itself 15 times.
use the power rule of exponents to create a simplified equivalent expression for (19^4)^9
To simplify (19^4)^9 using the power rule of exponents, we multiply the exponents:

(19^4)^9 = 19^(4 x 9) = 19^36

Therefore, a simplified equivalent expression for (19^4)^9 is 19^36.
you sure?
Yes, I'm sure. When the power rule is used to simplify an expression that takes the form (base^exponent1)^exponent2, the exponents are multiplied. Therefore, (19^4)^9 simplifies to 19^(4 x 9), which equals 19^36.
Apply the property of negative integer exponents to solve 7^-3. the answer should not contain any exponent expression or decimals.
The negative exponent property states that a^-b = 1/a^b. Therefore, we have:

7^-3 = 1/7^3 = 1/343.
Apply the property of negative exponents to generate an expression equivalent to 3^-17/8^-14 with positive exponents only.
To generate an equivalent positive exponent to 3^-17/8^-14 using the negative exponent property, we rewrite 3^-17 as 1/3^17 and 8^-14 as 1/8^14.

Therefore, the expression becomes:

1/3^17 * 8^14.

Or in other words:

8^14 / 3^17.
apply the properties of integer exponents to generate equivalent expressions to (7^-3)^7x7^20/6^-2 with only positive exponents, then solve the expression. provide the answer as an improper fraction.
To generate an equivalent expression to (7^-3)^7 x 7^20 / 6^-2 with only positive exponents, we should first handle 7^-3, 7^20, and 6^-2 separately.

For 7^-3, the negative exponent states that we shift the base to the denominator of a fraction and make the exponent positive, so it becomes 1/7^3, or 1/343.

Then we raise it to the power of 7, that is: (1/343)^7.

For 7^20, the exponent is already positive, so we keep it as it is.

And for 6^-2, we use the same rule for negative exponents that we used for 7^-3, and it becomes 1/6^2, or 1/36.

Now we can input these transformations into our initial equation:

(7^-3)^7x7^20 / 6^-2
= (1/343)^7 x 7^20 / 1/36
= (1/343^7) x 7^20 x 36.

Next, let's simplify:

= 1/343^7 x 7^20 x 36
= 1/117165996491^2 x 79766443076872509863361 x 36

Finally, this is simplified to integer 24817513279847098878344623104, however, we are asked as improper form so that we should keep this is in fraction form:

= 1/117165996491^2 x 79766443076872509863361 x 36 /1
= 79766443076872509863361 x 36 / 117165996491^2
= 28715951507714103566810819 / 13726080299741532938681